De læste og læsende køn - refleksioner over køn, litteratur og undervisning - Knudsen, Susanne V. (Kvinder, Køn & Forskning, 1999)
The article discusses three different tendencies of research in gender and literature. These are presented as sex, referring to the way we categorise women and men as biological beings; gender as construction; and deconstrudtion of gender binaries. These tendencies are applied to theories of aeshetic responses as Wolfgang Iser presents them in his book "The Act of Reading". Iser's focus on reading ad projection has inspired the author to improve three different tendencies of research on gender and literature. Throghout the article reflects on the use gender in reading and teaching literature; it offers no simple answer, but more possibilities.